Correlation Between Salivary Microbiome of Parotid Glands and Clinical Features in Primary Sjögren’s Syndrome and Non-Sjögren’s Sicca Subjects - Kim, Donghyun; Jeong, Ye Jin; Lee, Yerin; Choi, Jihoon; Park, Young Min; Kwon, Oh Chan; Ji, Yong Woo; Ahn, Sung Jun; Lee, Hyung Keun; Park, Min-Chan; Lim, Jae-Yol (Frontiers in Immunology, 2022)
Recent studies have demonstrated that the oral microbiome in patients with Sjögren's syndrome (SS) is significantly different from that in healthy individuals. However, the potential role of the oral microbiome in SS pathogenesis has not been determined. In this study, stimulated intraductal saliva samples were collected from the parotid glands (PGs) of 23 SS and nine non-SS subjects through PG lavage and subjected to 16S ribosomal RNA amplicon sequencing. The correlation between the oral microbiome and clinical features, such as biological markers, clinical manifestations, and functional and radiological characteristics was investigated. The salivary microbial composition was examined using bioinformatic analysis to identify potential diagnostic biomarkers for SS. Oral microbial composition was significantly different between the anti-SSA-positive and SSA-negative groups. The microbial diversity in SS subjects was lower than that in non-SS sicca subjects. Furthermore, SS subjects with sialectasis exhibited decreased microbial diversity and Firmicutes abundance. The abundance of Bacteroidetes was positively correlated with the salivary flow rate. Bioinformatics analysis revealed several potential microbial biomarkers for SS at the genus level, such as decreased Lactobacillus abundance or increased Streptococcus abundance. These results suggest that microbiota composition is correlated with the clinical features of SS, especially the ductal structures and salivary flow, and that the oral microbiome is a potential diagnostic biomarker for SS.